Analisa Pengaruh Hambatan Samping terhadap Kinerja Ruas Jalan pada Jalan Raya Kedu, Reco Kabupaten Wonosobo - M. Y, Zaki Firdausi; Husain, Maulana; Sari F, Mawada (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
According to the 1997 Indonesian Road Capacity Manual (MKJI), a road section is defined as the length of the road between and not influenced by major signalized or unsignalized intersections and has the same characteristics along the entire length of the road. Side obstacles are one of the factors causing traffic jams. Traffic jams are caused by an imbalance between the increase in vehicle ownership and the growth in available road infrastructure, as well as the effective capacity of existing road sections being smaller than the planned road capacity due to roadside obstacles. Traffic engineering is needed to monitor and maintain the continuity of transportation. According to the Institute of Transportation Engineers, USA, Traffic Engineering is a stage of transportation engineering which involves the design, geometric planning and traffic operations of all kinds of roads, road networks, terminals, surrounding land and relationships with other types of transportation.